Effect of decellularized spinal scaffolds on spinal axon regeneration in rats. Issue 3 (6th November 2017) - Zhu, Junyi; Lu, Yingfeng; Yu, Fangzheng; Zhou, Lebin; Shi, Jiawei; Chen, Qihui; Ding, Weili; Wen, Xin; Ding, Yu‐Qiang; Mei, Jin; Wang, Jian
Abstract: A series of complex influencing factors lead to failure of neural regeneration after spinal cord injury (SCI). Up to now, there is no robust treatment that can restore the loss of function caused by injury. Because damaged spinal axons do not spontaneously regenerate in their naturally inhibitory microenvironments, biomaterials that induce neural regeneration to appear as attractive treatments to improve the microenvironmental conditions after SCI. In this study, we report the novel use of decellularized (DC) scaffolds to provide contact guidance for axonal regrowth in vivo. The idea is that the scaffolds comprise some cytokines and a physical compartment that may facilitate regeneration. To evaluate the efficacy of scaffolds in supporting neural regeneration after SCI, the scaffold was implanted into an injured spinal cord of the rat. The injured spinal scaffolds showed a significant increase of the expression of GAP43, NF200, and Nestin in the scaffold implant groups compared with controls without the scaffold. In addition, the motor function has a better recovery. Together, these results demonstrate that spinal acellular scaffold is capable of promoting axonal regeneration after SCI and may serve as a potential tool in the treatment of SCI. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 698–705, 2018.